Enhancing the Protein, Mineral Content, and Bioactivity of Wheat Bread through the Utilisation of Microalgal Biomass: A Comparative Study of Chlorella vulgaris, Phaeodactylum tricornutum, and Tetraselmis chuii - Nancy Mahmoud; Joana Ferreira; Anabela Raymundo; Maria Cristiana Nunes (Applied Sciences, 2024)
At present, the incorporation of microalgae into bread and related cereal products has attracted attention due to their potential for enhancing nutritional profiles and their impact on health. In this study, 4% of Chlorella vulgaris, Phaeodactylum tricornutum, and Tetraselmis chuii were added into wheat flour to produce bread and assesses their impact on the dough rheology behaviour, quality performance, nutritive value, and bioactive profile of bread. The results showed that T. chuii strengthened the dough network, whereas P. tricornutum exerted minimal influence. Notably, the incorporation of C. vulgaris induced a pronounced weakening of the protein network within the dough matrix, leading to disruptions in dough structure and subsequent alterations in starch gelatinisation and retrogradation. These changes lead to a reduction in the bread volume (22.7%) and a corresponding increase in its firmness when C. vulgaris was added. In contrast, T. chuii and P. tricornutum had no significant effect on bread volume. All microalgae species caused the dark green colour of the bread and enhanced the bread nutritional composition, namely in terms of protein content (14.7% increase in C. vulgaris bread) and mineral profile. The breads containing T. chuii exhibited a noticeable increase in both total phenolic content (from 7.22 in the control to 38.52 (µg GAE/g)) and antioxidant capacity (from 117.29 to 591.96 (µg TEAC/g) measured by FRAP).